Laterality and unilateral deafness: Patients with congenital right ear deafness do not develop atypical language dominance. (December 2016) - Van der Haegen, Lise; Acke, Frederic; Vingerhoets, Guy; Dhooge, Ingeborg; De Leenheer, Els; Cai, Qing; Brysbaert, Marc
Abstract: Auditory speech perception, speech production and reading lateralize to the left hemisphere in the majority of healthy right-handers. In this study, we investigated to what extent sensory input underlies the side of language dominance. We measured the lateralization of the three core subprocesses of language in patients who had profound hearing loss in the right ear from birth and in matched control subjects. They took part in a semantic decision listening task involving speech and sound stimuli (auditory perception), a word generation task (speech production) and a passive reading task (reading). The results show that a lack of sensory auditory input on the right side, which is strongly connected to the contralateral left hemisphere, does not lead to atypical lateralization of speech perception. Speech production and reading were also typically left lateralized in all but one patient, contradicting previous small scale studies. Other factors such as genetic constraints presumably overrule the role of sensory input in the development of (a)typical language lateralization. Highlights: We examined sensory deprivation as an environmental cause of language laterality. Speech production, reading and auditory perception laterality were assessed. Congenital right-sided deaf patients were typically left dominant for language. Other factors overrule sensory influences when establishing lateralization.